Pengembangan Instrumen Evaluasi Keamanan Pangan dan Analisis Pengetahuan, Sikap, dan Perilaku Pedagang Pangan - Muhammad Syahrul Kurniawan; Nur Allimah Yunita; Winiati Pudji Rahayu; Lilis Nuraida (Badan Pengawas Obat dan Makanan, 2025)
To improve food safety in traditional markets, the Indonesian Food and Drug Authority (BPOM) has implemented the Community-Based Safe Food Market Program (Program Pasar Pangan Aman Berbasis Komunitas). The success of this program depends on the knowledge, attitudes, and behaviors of market stakeholders. This study aimed to develop and validate an evaluation instrument to assess these aspects and to apply it in markets where the program has been implemented. A questionnaire was developed through expert consultation, item validity and reliability testing, and final refinement. Validity testing involved 30 respondents from three traditional markets across Indonesia. The final instrument consisted of 30 items for market officers, 30 items for food vendors, and 20 items for market visitors, demonstrating acceptable validity and moderate to high reliability. The vendor questionnaire was administered using a total sampling approach. Survey results indicated that food vendors had good knowledge (8.0±1.04 out of 10), positive attitudes (41.00±2.04 out of 50), and appropriate food safety behaviors (42.64±3.25 out of 50). Correlation analysis revealed that only the length of time engaged in food vending was significantly associated with vendors’ knowledge, whereas no significant relationships were found for other characteristics. The findings indicate that the developed instrument is valid and reliable for assessing knowledge, attitudes, and behaviors related to food safety among traditional market communities. This instrument can be used to evaluate the effectiveness of the Community-Based Safe Food Market Program and to support evidence-based monitoring and continuous improvement of food safety interventions in traditional markets throughout Indonesia.